Public/privé : la (re)distribution des rôles dans la production des espaces publics à Paris et à Berlin - Antoine Fleury (Métropoles)
The present article focuses on the privatisation of public spaces in European metropoles (Paris, Berlin) in looking at task distribution between public and private actors. Confronting both cities sheds a new light on privatisation practices in European metropoles, at least as far as the private sector’s intervention in producing public spaces is concerned. Private actors intervene in relatively limited areas, with no general pattern. On the contrary, public investment in public spaces remains considerable. Furthermore, patterns form and modes of public action have been deeply renewed since the 1980s. Public action is still dominant, in association with various private actors however – economic actors, residents as well as city professionals. By opening up the decision-making process to local actors and residents, new privatisation tendencies take shape in European metropoles. Private interests thus have a growing influence on city councillors. This sometimes leads to contradiction s with other features of the city.